Correlation of death anxiety with coping strategies among Palestinian women with breast cancer: a cross-sectional study - Ahmead, Muna; Shehadah, Feda; Abuiram, Issa (Frontiers in Public Health, 2024)
Backgrounds: Death anxiety and maladaptive coping accompanied breast cancer diagnoses. Palestinian breast cancer patients' coping mechanisms and death anxiety have not been studied. Aim: To assess the prevalence of death anxiety and its relationship with coping strategies among Palestinian women with breast cancer attending Beit Jala Governmental Hospital in Bethlehem. Method: This study used a cross-sectional design. The study recruited 214 breast cancer patients who attended the Beit Jala Governmental Hospital in Bethlehem. The scales used included Templer's Death Anxiety Scale, and the Brief COPE Scale. To investigate the relationship between coping strategies and death anxiety, frequency, percentages, T-tests, and Pearson's correlation coefficient were used. Findings: The study found that 58.40% of breast cancer patients had death anxiety. Participants who used positive reframing (OR = 1.487, p-value = <.026), self-blame (OR =1.309, p-value = <.023) and religion (OR =1.260, p-value = <.031) as coping mechanisms were more likely to experience death anxiety. On other hand, using substances (OR =.657, p-value <.005) and active coping (OR =.629, p-value <.007) as coping strategies reduced the likelihood of experiencing death anxiety. Conclusion: The study revealed that breast cancer patients used a combination of functional and emotional coping strategies and that a significant proportion of these patients (58.4%) experienced symptoms of death anxiety. This study emphasizes the significance of screening for death anxiety and understanding the coping strategies utilized by breast cancer patients. This will assist in identifying patients who need more guidance and support.